The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11661-014-2187-3
|View full text |Cite
|
Sign up to set email alerts
|

An Atom Probe Study of Kappa Carbide Precipitation and the Effect of Silicon Addition

Abstract: The influence of silicon on j-carbide precipitation in lightweight austenitic Fe-30Mn-9Al-(0.59-1.56)Si-0.9C-0.5Mo cast steels was investigated utilizing transmission electron microscopy, 3D atom-probe tomography, X-ray diffraction, ab initio calculations, and thermodynamic modeling. Increasing the amount of silicon from 0.59 to 1.56 pct Si accelerated formation of the j-carbide precipitates but did not increase the volume fraction. Silicon was shown to increase the activity of carbon in austenite and stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 43 publications
3
57
0
2
Order By: Relevance
“…A model is applicable to predict the lattice misfit of these phases [19]. According to the orientation relationships between phases revealed by TEM (Figure 3 The low lattice misfit between κ-carbide and  grain is able to produce excellent mechanical properties [1,20,21]. On the other side, the low lattice misfit means small elastic strain energy.…”
Section: Resultsmentioning
confidence: 99%
“…A model is applicable to predict the lattice misfit of these phases [19]. According to the orientation relationships between phases revealed by TEM (Figure 3 The low lattice misfit between κ-carbide and  grain is able to produce excellent mechanical properties [1,20,21]. On the other side, the low lattice misfit means small elastic strain energy.…”
Section: Resultsmentioning
confidence: 99%
“…The quantum-mechanical structure optimizations are performed based on calculations of lowest-energy states of the electron structure and thus, are conducted at 0 K. Results from ab initio approaches employing DFT have offered good results that are in line with experimental evidence. For example, Mössbauer spectroscopy [17], atom-probe tomography (APT) [42], in situ synchrotron X-ray diffraction measurements [23], and correlative TEM/APT approaches [43] have shown that results from ab initio simulations employing DFT are applicable to systems containing nano-sized κ-carbides that are usually formed during isothermal annealing at temperatures of 600 • C and above. Generally speaking, the effect of temperature changes on the lattice parameter and on intrinsic material properties that derive from electron effects like electrical conductivity is often approximated to be linear [44].…”
Section: Methodsmentioning
confidence: 99%
“…Silicon was shown by ab initio calculations and experimental results to increase the activity of carbon in austenite and stabilize the j-carbide at higher temperatures. 18 The repulsive Si-C interaction was responsible for increasing the partitioning coefficient of carbon in j-carbide from 2.1 to 2.9 in 0.59% and 1.56% Si steels aged 60 h at 530°C. 18 Silicon was shown to partition to austenite during aging and decrease the austenite lattice parameter.…”
Section: Age Hardeningmentioning
confidence: 96%
“…18 This study used a combination of transmission electron microscopy (TEM), 3-D atom probe tomography (APT), x-ray diffraction (XRD), and first principles modeling to study the precipitation. In solution-treated specimens, XRD and TEM results confirmed that, regardless of Si content, no spinodal decomposition or short-range ordering within the austenite had taken place.…”
Section: Age Hardeningmentioning
confidence: 99%
See 1 more Smart Citation